Investigate the effectiveness of stop drill hole in delaying crack from crack initiation - Syafiq, Hashim (2012)
Many failures in engineering applications or machine components have been caused by a crack initiated from points at which stress was concentrated. As the stress concentration level is higher than a critical value, continuous crack-growth results in failure in the machine components. Crack initiation behavior has been evaluated to prevent an early failure of machine equipment. Delaying the crack initiation is important for the maintenance of machine elements as well as for the detection of crack initiation. Hence, the main objective of this study is to investigate the delay of crack using stop drilled holes. The investigation was based on the diameter of the stop drilled holes, the location of stop drilled hole and the ancillary stop hole drilled. The experiment and selected experiment on finite element analysis were done in order to validate the result. The experiment was carried out by using tensile test to obtain maximum applied load to the specimen while the finite element analysis was analyzed by using ALGOR software to obtain the stress of the specimen.The experimental results and the finite element analysis results show that the crack initiation life of the specimen was longer when the diameter of the stop drilled holes increased. The further the location of the stop drilled holes with the slits location, the longer crack initiation life of the specimen. The influence of extra stop-hole drill increase more time for delaying the crack on the specimen. From the experiment the longest time on delaying crack propagation is 92.32% increase compare before install stop-hole drill gained from Experiment 3. Thus, the influence of the stop drilled holes on the crack initiation life has been proved.